Added value of whole-genome sequencing for management of highly drug-resistant TB. (9th December 2014) - Outhred, Alexander C.; Jelfs, Peter; Suliman, Basel; Hill-Cawthorne, Grant A.; Crawford, Archibald B. H.; Marais, Ben J.; Sintchenko, Vitali
Abstract: Objectives: Phenotypic drug susceptibility testing (DST) for Mycobacterium tuberculosis takes several weeks to complete and second-line DST is often poorly reproducible, potentially leading to compromised clinical decisions. Following a fatal case of XDR TB, we investigated the potential benefit of using whole-genome sequencing to generate an in silico drug susceptibility profile. Methods: The clinical course of the patient was reviewed, assessing the times at which phenotypic DST data became available and changes made to the therapeutic regimen. Whole-genome sequencing was performed on the earliest available isolate and variants associated with drug resistance were identified. Results: The final DST report, including second-line drugs, was issued 10 weeks after patient presentation and 8 weeks after initial growth of M. tuberculosis . In the interim, the patient may have received a compromised regimen that had the potential to select for further drug resistance. The in silico susceptibility profile, extrapolated from evolving evidence in the literature, provided comparable or superior data to the DST results for second-line drugs and could be generated in a much shorter timeframe. Conclusions: We propose routine whole-genome sequencing of all MDR M. tuberculosis isolates in adequately resourced settings. This will improve individual patient care, monitor for transmission events and advance our understanding of resistance-associated mutations.